Defect-Engineered Metal-Organic Frameworks - Fang, Zhenlan; Bueken, Bart; De Vos, Dirk E.; Fischer, Roland A. (Angewandte Chemie International Edition, 2015)
Defect engineering in metal–organic frameworks (MOFs) is an exciting concept for tailoring material properties, which opens up novel opportunities not only in sorption and catalysis, but also in controlling more challenging physical characteristics such as band gap as well as magnetic and electrical/conductive properties. It is challenging to structurally characterize the inherent or intentionally created defects of various types, and there have so far been few efforts to comprehensively discuss these issues. Based on selected reports spanning the last decades, this Review closes that gap by providing both a concise overview of defects in MOFs, or more broadly coordination network compounds (CNCs), including their classification and characterization, together with the (potential) applications of defective CNCs/MOFs. Moreover, we will highlight important aspects of “defect‐engineering” concepts applied for CNCs, also in comparison with relevant solid materials such as zeolites or COFs. Finally, we discuss the future potential of defect‐engineered CNCs. Designer defects: Defects in coordination network compounds (CNCs) are defined as “sites that locally break the regular periodic arrangement of atoms or ions of the static crystalline parent framework due to missing or incorrectly dislocated atoms or ions”. This Review provides both a concise overview of defects in CNCs (including their classification and characterizations) and applications of defective CNCs/MOFs.